Determinants and Policy Simulation of Firms Cooperation in Innovation - Almas Heshmati; Flávio Lenz-Cesar (Institute for the Study of Labor (IZA), 2013)
This research introduces an agent-based simulation model representing the dynamic processes of cooperative R&D in the manufacturing sector of South Korea. Firms' behavior is defined according to empirical findings on the Korean Innovation Survey 2005 and captured in a multivariate probit regression model. The econometrics model identifies the determinants on firms' likelihood to participate in cooperation with other organizations when conducting innovation activities. These determinants are translated into simulation parameters which are calibrated to the point that the simulated artificial world are equivalent to the one observed in the real world. The aim of the simulation game is to investigate the differences in sector responses to internal and external changes, including cross-sector spillovers, when applying three different policy strategies to promote cooperation in innovation. The findings indicate possible appropriate (or non-appropriate) policy strategies to be applied depending on the target industries.
Keywords: C15; C71; D21; D85; L20; O31; 330; agent-based simulation; collaborative R&D; innovation networks; simulation game; policy strategy